Commodity Price Effects on Currencies - Yin-Wong Cheung; Wenhao Wang (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using quarterly data on four commodity exporting countries, we study the explanatory power of real commodity prices for predicting real effective exchange rates, with special attention to the separate roles of different sectoral commodity prices during alternative time periods. We find that the commodity price effect is non-uniform across countries and commodity sectors, and moreover varies over time. The use of fixed weight price indexes, or nominal exchange rates and commodity prices, also yields heterogeneous commodity price effects. Further, the pattern of commodity price effects is influenced by the presence of macroeconomic conditions, the effects of crises, and the exchange rates of top trading partners. These empirical results highlight the challenges of explaining a wide range of currency behaviors across different time periods with a single commodity-price-based exchange rate model. These findings also complicate the tasks facing policymakers who assume stable commodity price effects.
Keywords: F31; F41; 330; commodity currencies; sectoral commodity prices; The US Dollar Effect; The Global Financial Crisis; macro variables